Bone-to-Brain: A Round Trip in the Adaptation to Mechanical Stimuli - Gerosa, Laura; Lombardi, Giovanni (Frontiers in Physiology, 2021)
Besides the classical ones (support/protection, hematopoiesis, storage for calcium and phosphate) multiple roles emerged for bone tissue, definitively making it an organ. Particularly, the endocrine function, and in more general terms, the capability to sense and integrate different stimuli and to send signals to other tissues, has highlighted the importance of bone in homeostasis. Bone is highly innervated and hosts all nervous system branches; bone cells are sensitive to most of neurotransmitters, neuropeptides, and neurohormones that directly affect their metabolic activity and sensitivity to mechanical stimuli. Indeed, bone is the principal mechanosensitive organ. Thanks to the mechanosensing resident cells, and particularly osteocytes, mechanical stimulation induces metabolic responses in bone forming (osteoblasts) and bone resorbing (osteoclasts) cells that allow the adaptation of the affected bony segment to the changing environment. Once stimulated, bone cells express and secrete, or liberate from the entrapping matrix, several mediators (osteokines) that induce responses on distant targets. Brain is a target of some of these mediator (e.g., osteocalcin, lipocalin2, sclerostin, Dkk1, fibroblast growth factor 23), as most of them can cross the blood-brain barrier. For others, a role in brain has been hypothesized, but not yet demonstrated. As exercise effectively modifies the release and the circulating levels of these osteokines, it has been hypothesized that some of the beneficial effects of exercise on brain functions may be associated to such a bone-to-brain communication. This hypothesis hides an interesting clinical clue: may well-addressed physical activities support the treatment of neurodegenerative diseases, such as Alzheimer’s and Parkinson’s diseases?